Bussiness Model Canvas: Portable Watering Tools / Ain Amalina Kamarulanuar - Kamarulanuar, Ain Amalina (2020)
The Value Proposition is an innovation, service, or feature intended to make a company or product attractive to customers. It is the segment that compelling about the proposition of my product of why do the target segment need to buy the portable watering tools. For this product, there are some value propositions that can be identified.